The Interplay of Perceptions and Conflict Behaviors during Disagreements: A Daily Study of Physical Teen Dating Violence Perpetration - Fortin, Andréanne (Journal of interpersonal violence, 2022)
Physical dating violence (DV) is a widespread problem among adolescents. A growing body of literature demonstrates that physical DV often occurs during disagreements when partners use destructive conflict management strategies, such as conflict engagement (e.g., losing control, criticizing) or withdrawal (e.g., acting cold, being distant). However, little is known regarding how the individual daily variability on the use of destructive conflict management strategies can influence the probability of perpetrating day-to-day physical DV, especially if the other partner is also perceived as using destructive behaviors. Using an intensive longitudinal approach, the current study first aimed to examine the daily associations between the use of various conflict management strategies and physical DV perpetration in adolescent dating relationships. A second objective was to investigate if perceived partner?s conflict behaviors moderated the relation between self-reported conflict management strategies and day-to-day physical DV perpetration. A sample of 216 adolescents (Mage = 17.03, SD = 1.49) involved in a dating relationship, completed a baseline assessment followed by 14 daily diaries. Results of multilevel logistic analyses revealed that using conflict engagement strategies significantly increased the probability of day-to-day physical DV perpetration. Furthermore, the probability of perpetrating physical DV was significantly higher on days in which teens reported using high levels of conflict engagement while also perceiving their partner as using high levels of conflict engagement or withdrawal. These findings yield new insights on the daily context in which disagreements might escalate into aggression. Evidence from this study further supports the conflict escalation pattern and the demand/withdraw communication pattern in the context of adolescent dating relationships. Preventive initiatives should address the interplay of perceptions and conflict behaviors concerning physical DV perpetration.